2020
DOI: 10.3389/fcell.2020.00289
|View full text |Cite
|
Sign up to set email alerts
|

H3K4me1 Distribution Predicts Transcription State and Poising at Promoters

Abstract: Monomethylation on lysine 4 of histone H3 (H3K4me1) is commonly associated with distal enhancers, but H3K4me1 is also present at promoter regions proximal to transcription start sites. To assess a possible role for H3K4me1 in dictating gene regulatory states at promoters, we examined H3K4me1 peak density around promoters in human and mouse germ cells using an analytic strategy that allowed us to assess relationships between different epigenetic marks on a promoter-by-promoter basis. We found that H3K4me1 exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 39 publications
8
72
1
Order By: Relevance
“…H3K4Me3 had the highest intensity consistent with expectations (Guenther et al, 2007) followed by H3K27ac. Some studies show a bimodal distribution of H3K4Me1 and/or H3K4Me3 signal at promoters (Barski et al, 2007;Kingsley et al, 2020) but this is not always observed (Hoffman et al, 2010;Bae and Lesch, 2020). In this study only a very slight bimodal distribution in the profile of H3K4Me3, H3K4Me1, and H3K27ac was observed.…”
Section: Discussioncontrasting
confidence: 61%
“…H3K4Me3 had the highest intensity consistent with expectations (Guenther et al, 2007) followed by H3K27ac. Some studies show a bimodal distribution of H3K4Me1 and/or H3K4Me3 signal at promoters (Barski et al, 2007;Kingsley et al, 2020) but this is not always observed (Hoffman et al, 2010;Bae and Lesch, 2020). In this study only a very slight bimodal distribution in the profile of H3K4Me3, H3K4Me1, and H3K27ac was observed.…”
Section: Discussioncontrasting
confidence: 61%
“…In addition, the TSS clusters located at gene TSS are marked with a bimodal H3K4me1 pattern which indicates active promoters, in contrast to the others that are marked with relatively unimodal H3K4me1 pattern which indicates active enhancers 38,39 . In summary, the SCAFE TSS classifier robustly distinguishes genuine TSS from artifacts.…”
Section: Tss Identification Using Sc-end5-seq Methodsmentioning
confidence: 99%
“…H3K4me1 is commonly associated with distal enhancers, but it is also present at promoter regions proximal to transcriptional start site ( Cheng et al, 2014 ; Bae and Lesch, 2020 ). Noteworthy, H3K4me1 peak density was recently examined around promoters in human and mouse germ cells ( Bae and Lesch, 2020 ).…”
Section: Histone Modifications and The Ntt-mmp-2 Isoform Expressionmentioning
confidence: 99%
“…H3K4me1 is commonly associated with distal enhancers, but it is also present at promoter regions proximal to transcriptional start site ( Cheng et al, 2014 ; Bae and Lesch, 2020 ). Noteworthy, H3K4me1 peak density was recently examined around promoters in human and mouse germ cells ( Bae and Lesch, 2020 ). H3K4me1 was found to exhibit either a bimodal pattern at active promoters, where it flanks H3K4me3, or a unimodal pattern at poised promoters, where it coincides with both H3K4me3 and trimethylation at lysine 27 of histone H3 (H3K27me3).…”
Section: Histone Modifications and The Ntt-mmp-2 Isoform Expressionmentioning
confidence: 99%
See 1 more Smart Citation